2021
DOI: 10.1021/acs.biomac.1c00683
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Poly(ε-caprolactone) Diacrylate for Micelle-Cross-Linked Sodium AMPS Hydrogel for Use as Controlled Drug Delivery Wound Dressing

Abstract: This study focuses on the synthesis of poly­(ε-caprolactone) diacrylate (PCLDA) for the fabrication of micelle-cross-linked sodium AMPS wound dressing hydrogels. The novel synthetic approach of PCLDA is functionalizing a PCL diol with acrylic acid. The influences of varying the PCL diol/AA molar ratio and temperature on the suitable conditions for the synthesis of PCLDA are discussed. The hydrogel was synthesized through micellar copolymerization of sodium 2-acrylamido-2-methylpropane sulfonate (Na-AMPS) as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 71 publications
(133 reference statements)
1
10
0
Order By: Relevance
“…Cell proliferation was detected by CCK-8 assay, and the untreated group was set as the control group. Results are shown in Figure C; after being cultured with the hydrogel extract for 1 and 2 days, the activity of L929 cells in all hydrogel groups was above 70%, which is in compliance with international biomaterial standards (ISO10993:2009) . In addition, the bright green fluorescence specific labeling live cell was observed in all hydrogel groups, indicating that these QCS/TA hydrogels were cyto-compatible in vitro (Figure D).…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…Cell proliferation was detected by CCK-8 assay, and the untreated group was set as the control group. Results are shown in Figure C; after being cultured with the hydrogel extract for 1 and 2 days, the activity of L929 cells in all hydrogel groups was above 70%, which is in compliance with international biomaterial standards (ISO10993:2009) . In addition, the bright green fluorescence specific labeling live cell was observed in all hydrogel groups, indicating that these QCS/TA hydrogels were cyto-compatible in vitro (Figure D).…”
Section: Resultssupporting
confidence: 65%
“…Results are shown in Figure 8C; after being cultured with the hydrogel extract for 1 and 2 days, the activity of L929 cells in all hydrogel groups was above 70%, which is in compliance with international biomaterial standards (ISO10993:2009). 62 In addition, the bright green fluorescence specific labeling live cell was observed in all hydrogel groups, indicating that these QCS/TA hydrogels were cyto-compatible in vitro (Figure 8D). The superior performance of the QCS/TA 2.5 hydrogel encouraged us to assess its biocompatibility in vivo.…”
Section: Biocompatibility Of Hydrogelsmentioning
confidence: 78%
“…The Korsmeyer‐Peppas model, based on the exponent of the power law ( M t / M ∞ = kt n ), gave information regarding the release mechanism of the encapsulated drug from the matrix based on the value of n . For the case of a cylindrical matrix, n < 0.5 corresponds to pseudo‐Fickian diffusion, n = 0.5 is Fickian diffusion, 0.5 < n < 1.00 defines anomalous (non‐Fickian) transport and n = 1.00 signifies zero‐order release 19,22 . Thus, the release of curcumin‐loaded hydrogels at concentrations of 800, 1400, 1900 and 2200 μg mL −1 was characterized as non‐Fickian transport, which indicated that drug release is controlled by more than one process, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…The preparations of the prodrugs, however, are relatively complex and involve various steps; thus, direct loading is preferably employed because of its simple preparation method. To establish effective drug delivery materials, mathematical models have been applied to define and predict the comprehension of all the phenomena involving release kinetics, such as diffusion through the polymeric matrices, desorption of drug bound to the surface, polymer matrix erosion, a combined erosion‐diffusion process etc 18,19 . The carriers must be sufficiently stable to prohibit burst or rapid delivery but biologically degradable over an appropriate duration to allow controllable release and prolong the circulation time of the drug.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation